Digitalization and Church Leadership: Challenges and Opportunities for Contemporary Evangelism - Natan, Antonius; Ming, David; James, Jonathan D. (Jurnal Teologi (JUTEOLOG), 2025)
In the rapidly evolving digital era, church leadership and evangelistic missions face both significant challenges and new opportunities that demand strategic adaptation and technological innovation. The implementation of the Great Commission—including evangelism, apostolic ministry, pastoral care, discipleship, and church multiplication—must align with digital dynamics, especially in contexts constrained by geography, time, and limited human resources. Contemporary church leaders are required to possess not only the ability to discern the boundaries of their ministry but also the skill to delegate responsibilities wisely and collectively. This paper explores a collaborative model of church leadership grounded in biblical principles, as illustrated by the Apostle Paul in 1 Corinthians 3:6 (NIV): “I planted the seed, Apollos watered it, but God has been making it grow.” Through both theological and practical approaches, this study maps out a ministry structure that fosters communal learning within the body of Christ. The primary aim is to build effective ministerial synergy that supports sustainable church growth and the expansion of the gospel message. By strategically utilizing digital media—including social platforms, video content, and interactive applications—churches can enhance the effectiveness of their communication and outreach. This paper highlights the urgency of cross-functional collaboration and digital innovation in church leadership as a response to the realities of mission in the digital age.